Sosialisasi Sistem Pemantauan Tempat Sampah Pintar Secara Real-Time Berbasis IoT di SMAN 1 Kepahiang - Yoli Andi Rozzi; Siswanto Siswanto; Jhoanne Fredericka; Nofi Qurniati; Hendi Raden Wijaya (Jurnal Dehasen Untuk Negeri, 2024)
Community service activities in the form of socialization and practice regarding IoT-based Real-Time Smart Trash Monitoring System simulations have the aim of providing knowledge and information to students at SMAN 1 Kepahiang Regency so that they gain knowledge about current technological advances. The subjects of this service activity were students at SMAN 1 Kepahiang Regency. The socialization process is carried out by providing information and direct practice in assembling IoT-based Real-Time Smart Trash Monitoring simulation components. Where the IoT-based Real-Time Smart Trash Monitoring System simulation is an example of the implementation of artificial intelligence. In practice, the system will use a microcontroller for data processing. Then the result of this community service activity is that students at SMAN 1 Kepahiang Regency will gain knowledge about current technological advances. Apart from that, students at SMAN 1 Kepahiang Regency are also expected to be able to develop more creative and innovative ideas related to technological developments. that exists. The conclusion obtained from carrying out community service activities, especially students at SMAN 1 Kepahiang Regency, is in the form of gaining knowledge and information regarding the Real-Time IoT Based Smart Trash Monitoring System.